Developmental Population Pharmacokinetics and Dosing Optimization of Cefepime in Neonates and Young Infants - Zhao, Yang; Yao, Bu-Fan; Kou, Chen; Xu, Hai-Yan; Tang, Bo-Hao; Wu, Yue-E; Hao, Guo-Xiang; Zhang, Xin-Ping; Zhao, Wei (Frontiers in Pharmacology, 2020)
Objective: Cefepime is used to treat severe infections in neonates. Pharmacokinetic data have only been evaluated among preterm neonates and population pharmacokinetic model lacked external validation. Hence, our aim is to obtain the population pharmacokinetic parameters of cefepime with large sampling and optimize the cefepime dosage regimen for neonatal infection based on developmental pharmacokinetics-pharmacodynamics. Methods: Blood samples from neonates and young infants treated with cefepime were collected using the opportunistic sampling design. The concentration of cefepime was determined using high performance liquid chromatography with ultraviolet detection. The population pharmacokinetic model was established using NONMEM software. Results: One hundred blood samples from eighty-five neonates were analyzed. The population pharmacokinetics of cefepime were described by a one-compartment model with first-order elimination. Covariate analysis indicated that serum creatinine concentration, postmenstrual age and current weight had significant impact on the pharmacokinetic parameters of cefepime. Monte Carlo simulation results showed that the current dosage regimen (30mg/kg, q12h) had a high risk of insufficient dose. For 70% of neonates to obtain a higher free drug concentration than the minimum inhibitory concentration during 70% of the dosing interval, 50 mg/kg q12h was needed with a susceptibility breakpoint of 4 mg/L. For a minimum inhibitory concentration of 8 mg/L, 40 mg/kg q8h was recommended for all neonates. Conclusion: A population pharmacokinetic model of cefepime in neonates and young infants was established. According to simulation results based on the developmental pharmacokinetics-pharmacodynamics, different dosage regimens should be given depending on pathogens and the postmenstrual age.